Simulating the evolution of soil solutions in irrigated rice soils in the Sahel - (:unkn) unknown (My University, 2009)
In Sahelian countries, agriculture often relies on irrigation especially for rice cropping which has been introduced these last decades. As most of the water resources used for irrigation (mainly rivers and lakes) have an alkaline composition, rice cropping is often held as responsible for soil alkalinization. In order to evaluate the probability for this process to occur, we studied 3 different sites in West Africa where numerical simulation of the geochemical interactions between soil, irrigation water and groundwater were performed with PHREEQC. It was possible to simulate the evaporation of the ponding water, the mixing between groundwater and irrigation water, the lateral drainage (flushing) and the leaching, and finally the management of the crop residues. By performing prospective simulations over 60 cropping cycles it has been shown that soil alkalinization and sodication are not inevitable in these areas especially if the cropping is properly managed. Moreover, when straw is removed and the plot flushed before the new cropping season, alkaline soils can even be improved with rice cropping.
Keywords: African Research